Java Ethnic Communication In Religious Life In The City Of Medan - Junaidi Junaidi (Proceeding International Seminar of Islamic Studies, 2019)
Javanese are ethnic who are unique in their communication life. Called unique because of the habits of the ethnic Javanese followed by other ethnic groups. This paper reveals Javanese ethnic communication in religious life in Medan. The question in this paper is how is Javanese ethnic communication in religious life in Medan? In order to answer these questions, the way to do this is by conducting interviews with Javanese in their communication activities.From the interviews conducted information obtained that in communication activities in religious life, Javanese Ethnic pay attention to ethics or norms adopted. Javanese ethnicity does not impose its will in practicing every teaching. But more gently appealed to the other ethnic groups invited to feel touched and finally try to follow the habits practiced by the Javanese in religious life. And nonverbally, the Javanese ethnic's face when carrying out communion activities is accompanied by a warm smile so that opponents speak comfortable.